Serviços de apoio na Educação Física escolar: atuação do professor especialista em Educação Física Adaptada - Camargo, Laureen Lopes (Universidade Federal de São Carlos, 2022)
From the perspective of Special Education (SE), Brazilian legal provisions ensure some supports’ types for students with disabilities (SWD) in regular education systems. However, when considering Physical Education (PE) classes, which have specific conditions and different features from those of regular classrooms, it is necessary to think about who should become the professional responsible for this support. In some countries, there is a specialist teacher in Adapted Physical Education (APE), who provides support services for PE at school, however, in Brazil, this presence is still not common. Thus, this research aimed to analyze the possibilities and limits of the role of the specialist teacher in APE in inclusive contexts in Brazilian Basic Education. Its specific objectives were: 1) to identify what the educational legislation, in different governmental spheres, and the Brazilian and international academic literature, offer with regard to support services and specialized professionals aimed at SWD, in PE classes; and 2) to elaborate, develop and analyze a proposal of inclusion support services offered by the specialist teacher in APE, to the different actors involved in the inclusion process in PE classes, in a public municipal education network in the countryside of São Paulo (SP). As method, the collaborative research was selected and it involved the participation of a pair formed by a PE teacher (n=1), who met the inclusion criteria, and the researcher, who work in the same school municipal education network. For data collection, four stages were defined: I. Approximation, Communication; II. Co-planning; III. Collaborative Action, and IV. Co-evaluation, using as procedures: two interviews - initial and final; systematic observation and field diary; and as instruments their respective scripts. For data treatment, thematic analysis and three reliability criteria were adopted (intra-judge agreement, member checking, and data triangulation). As results, it was elaborated and analyzed through the collaborative action between the research participants, a proposal of inclusion support services that can be offered by the specialist teacher in APE, to the different actors involved in PE classes, establishing some general guidelines and indicating possible attributions, roles, responsibilities and strategies, directed to the Brazilian context, based on the consulting, itinerancy, and co-teaching approaches. Finally, it was verified that benefits were promoted not only to SWD, but to all students and to the research participant PE teacher, and that these services should be performed by expert teachers properly qualified with 1) pre-service teacher training in the area of PE; 2) recognized experience and performance with people with disabilities in PE classes at school and in various fields of APE; and, initially, 3) with specialization at the Stricto Sensu Graduate level, in the area of SE and/or APE. In conclusion, the urgency for creating independent Stricto Sensu Graduation Programs in APE and the need for implementation of specialist teachers in APE, as well as the insertion of this professional in regular education networks, was identified, so that they belong to the support networks and are offered the specialized support services needed to the specifics of PE classes.
Support services in school Physical Education: performance of the specialist teacher in Adapted Physical Education
Keywords: Educação Especial; Educação Física Escolar; Professor Especialista; Colaboração; Estudantes com Deficiência; Special Education; School Physical Education; Specialist Teacher; Collaboration; Students with Disabilities; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO